The forties in Islamic inheritance (view and criticism) - يعقوب يوسف محمد / قاسم بستاني ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research in the forties and the works classified therein, including all forty hadiths on various topics and differentissues, deserve attention and research because it has become a great Islamic heritage in various scientific and practical fields due to its connection to the intellectual, creed, educational, moral, political and social aspects.  to other aspects of life